Conscious Techniques Affected the Adolescent’s Ability In Early Breast Cancer Detection - Mujito; Andi Andi Hayyun Abiddin; Diwin Amaliyah; Ning Arti Wulandari (Journal of Ners and Midwifery, 2024)
Breast cancer is a malignant tumor and grows in the breast tissue resulting in death. Breast cancer prevention by means of breast self-examination. This study aimed to determine the effect of video media on conscious techniques with a combination of demonstrations on the practical ability of adolescents in early detection of breast cancer. The method used a quasi-experimental design, non-equivalent control group design with a population of 279 and a sample of 40 respondents with inclusion criteria of young women, aged 16 years as students of SMA Negeri 1 Tarik Sidoarjo. The data collection measured skills in 2 groups of respondents. The experimental intervention group used videos and demonstrations, while the intervention control group used lectures and leaflets. The intervention was done in 1 day, the posttest was conducted 7 days after the intervention. The results showed that the average value of the pretest posttest of the two groups increased. The results of the statistical test paired T-Test obtained a significant value of p-value = (0.000 < 0.05) meant that there was an effect of providing video media with conscious techniques with a combination of demonstrations on the practical ability of adolescents in early detection of breast cancer. Educators should develop programs to improve skills for early detection of breast cancer, in collaboration with health workers through health promotion so that all students are aware of health.